The practice of research in social work - Engel, Rafael J (SAGE, 2013)
Includes bibliographical references (pages 454-470) and index; Designed to help students develop skills in evaluating research and conducting studies, the Third Edition of this popular text makes principles of evidence-based practice come alive through illustrations of actual social work research. The authors introduce students to the study of research in social work and to the contributions made to our understanding of what is effective social work practice. In addition, the authors have designed this edition to directly and indirectly help students achieve the six core competencies identified by CSWE as essential to competency-based education. --Publisher description; 1. Science, society, and social work research -- 2. The process and problems of social work research -- 3. Ethical and scientific guidelines for social work research -- 4. Measurement -- 5. Sampling -- 6. Causation and research design -- 7. Group experimental designs -- 8. Single-subject design -- 9. Survey research -- 10. Qualitative methods: observing, participating, listening -- 11. Qualitative data analysis -- 12. Mixing and comparing methods and studies -- 13. Evaluation research -- 14. Quantitative data analysis -- 15. Reporting research -- Appendix A : Questions to ask about a research article -- Appendix B : How to read a research article -- Appendix C : Table of random numbers